2008
DOI: 10.1007/s00406-008-0819-6
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempters: biological stressmarkers and adverse life events

Abstract: j Abstract Risk factors for suicidal behaviour include adverse life events as well as biochemical parameters acting, e.g. within the hypothalamic-pituitary-adrenal axis and/or monoaminergic systems. The aim of the present investigation was to study stressful life events and biological stress markers among former psychiatric inpatients, who were followed up 12 years after an index suicide attempt. At the time of the index suicide attempt, and before treatment, cerebrospinal fluid (CSF) samples were taken, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…These specific GRSEs (from nonfamily members) appear to cause MSM to think about, plan, or attempt suicide. Suicide may appear to be a solution to the difficulties and stress from these events, or stress may aggravate underlying psychiatric conditions and thereby promote suicidal behaviors (Sivasubramanian et al, ; Meyer, ; Hatzenbuehler, ; Sunnqvist, Westrin, & Traskman‐Bendz, ). To our best knowledge, the present study is the first report to an association between different specific types of GRSEs and suicidal behaviors in Chinese MSM.…”
Section: Discussionmentioning
confidence: 99%
“…These specific GRSEs (from nonfamily members) appear to cause MSM to think about, plan, or attempt suicide. Suicide may appear to be a solution to the difficulties and stress from these events, or stress may aggravate underlying psychiatric conditions and thereby promote suicidal behaviors (Sivasubramanian et al, ; Meyer, ; Hatzenbuehler, ; Sunnqvist, Westrin, & Traskman‐Bendz, ). To our best knowledge, the present study is the first report to an association between different specific types of GRSEs and suicidal behaviors in Chinese MSM.…”
Section: Discussionmentioning
confidence: 99%
“…higher cortisol peaks) following social or novel stimui than their ‘normotypic’ peers, paralleling individuals severely stressed in youth, even without a prior history of severe stress exposure (Lopez-Duran et al, 2009; Corbett et al, 2010; Spratt et al, 2012; Schupp et al, 2013). This low HPA axis resilience can have profound long-term impacts on social behavior, and may also increase the risk of suicide (Sher, 2006; Sunnqvist et al, 2008; Garlow et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cluster of features comprising impulsivity, mood reactivity, self-injury, suicidality, and dissociation has been proposed to illustrate the susceptibility of BPD patients to maladaptive stress responses (Zimmerman & Choi-Kain, 2009). Adult personality psychopathology (Brodsky, Malone, Ellis, Dulit, & Mann, 1997) and suicide attempts as well as completed suicides are associated with childhood trauma in the form of severe neglect (Glaser, 2000) and sexual or physical abuse (Dinwiddie et al, 2000; Jokinen et al, 2010; Sunnqvist, Westrin, & Träskman-Bendz, 2008; Ystgaard, Hestetun, Loeb & Mehlum, 2004), probably mediated through dysregulated neurobiological stress systems (De Bellis, Spratt, & Hooper, 2011), aggressive traits (Sarchiapone et al, 2009), and family dynamics (Brodsky et al, 2008). It has been suggested that childhood maltreatment may mold the phenotypic characteristics of psychopathology, yielding a variety of ecophenotypes (Teicher & Samson, 2013).…”
mentioning
confidence: 99%